Analisis Semiotic Analysis in the Short Story "Ingan" by Heri Sucipto - Halimah; Syaiful Arifin; ulwatunnisa, marwah; Meita Setyawati (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
The short story entitled Ingan by Heri Sucipto is special, namely that it describes the beauty and noble values ​​of the island of Kalimantan, as well as a person's struggle to achieve their dreams. Therefore, this short story needs to be studied, especially the signs that provide meaning in the short story. The aim of this research is to describe the Index, Icons and Symbols in the short story Ingan by Heri Sucipto through semiotic studies. This research is a qualitative descriptive study. Based on the research results, there are semiotic elements, namely indices, icons, symbols and indexes. There are five data icons, namely the words wilderness, virgin, slender, berhanyut larung, and inner struggle. The index is 15, namely the words awesome, graduation, leaving, respected, seriously ill, surprised, made me realize, dislike, accept, marriage, emotion, sobbing, limiting, crowding, and crying. There are seven symbols, namely the words edge city, oil city, borneo land, lamin, apple city, simalakama fruit, and graduation